Voices from the Barzakh: A Sociological Reading of Refugee Suffering in Omayma Abdullah’s al-Ṭarīq 'abra al-Barzakh: Suara dari Barzakh: Pembacaan Sosiologis tentang Penderitaan Pengungsi dalam Karya Omayma Abdullah, al-Ṭarīq 'abra al-Barzakh - Azkiyatunnisa; Ulil Abshar; Ekawati; Fitri Liza; Mawardi Mawardi; Deva Yohana (ELOQUENCE : Journal of Foreign Language, 2025)
Background: The short story al-Ṭarīq 'abra al-Barzakh is a literary work that reflects the suffering of Sudanese refugees during the 1956–2005 conflict, which is important to study. Purpose: This study aims to analyze the forms of suffering experienced by Sudanese refugees in the short story “al-Ṭarīq 'abra al-Barzakh.” Method: This study uses a library method, with the short story al-Ṭarīq 'abra al-Barzakh as the primary data source. The analysis focuses on textual elements such as narrative, dialogue, and description. Wellek and Warren's the sociology of content of the literary work approach is used, supported by Agamben's theory of bare life to understand how the suffering of refugees is represented in the story. Result and Discussion: The results of the study show five forms of suffering, namely physical, psychological, social, existential, and spiritual. This is caused by the collapse of Sudan's socio-political structure, which places refugees in a state of bare life, namely biological existence without social or legal protection. This forces refugees to live without protection, without a country, and without access to basic needs. Conclusions and Implications: This study shows that short stories function as social documents that record the tragedy of displacement while also showing how humans are reduced to bare life in situations of war. The implications of this study emphasize the importance of literature as a medium of collective memory and a means of understanding trauma, marginalization, and the dynamics of humanity in the study of displacement.